(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
Given the importance of intervening in children’s and adolescents’ behavior problems, several intervention programs with parents were developed. This study aim to describe effects of a group intervention based on multiple evaluations and instruments that attempted to improve parental social competence and prevent behavior problems. Twelve mothers/fathers of children and adolescents and two mothers with adult children participated in the parenting program. Data collection for pre and pos-intervention evaluations and follow up investigated parental social educational skills (HSE-P), general social skills and behavior problems. During group sessions various themes about HSE-P were discussed, such as expressing positive feelings, having conversation, negotiating, establishing rules, and others. Results showed that the frequency of HSE-P and social skills improved whereas behavior problems decreased. Limitations and contributions of this research are presented.